Household food insecurity and associated factors among rural and urban high school students in Kurdish population of Iran - Arzhang, Pishva; Pourghassem Gargari, Bahram; Sarbakhsh, Parvin; Farzaneh, Hamid (Progress in Nutrition, 2020)
Objective: There is limited information in Kurdish-inhabited areas of Iran on the prevalence of food insecurity, dietary patterns, and socioeconomic factors that are related to food insecurity. We investigated mentioned factors among Kurdish population, focusing on high school students and their families. Study design: Cross sectional study Design: A cross-sectional study on 364 high-school students and their families was done. Food insecurity was evaluated with the use of the USDA 18-Item Household Food Security Questionnaire. Food insecurity, food frequency questionnaires and socio-economic(the combination or interaction of social and economic factors) data were filled out during face to face interviews with students and their mothers. Results: The overall food insecurity prevalence in the studied population was 41.8% (38.4% and 49.1% for urban and rural areas, respectively). There were three dietary patterns in the studied subjects. In the studied subjects food insecurity was associated with dietary pattern (P<0.05). Food insecurity was associated with father’s job, mother’s job, father’s education, mother’s age, household’s economic status, and grade point average. Conclusion: Food insecurity is common and is in the range of other part of Iran among Iranian Kurdish population. Associations between food insecurity, dietary pattern, parents related factors and economic status demonstrated.